Intermediate accounting - Rees, Lynn L. (Thomson/South-Western, 2004)
Designed for the intermediate financial accounting course, this text focuses on relating accounting concepts to accounting practice. Of the book's 21 chapters, eight are devoted to the FASB's Conceptual Framework and accounting concepts. This conceptual approach is consistent with the call for a focus on learning instead of memorizing